Dual antiplatelet therapy with aspirin and clopidogrel for acute high risk transient ischaemic attack and minor ischaemic stroke: a clinical practice guideline. (18th December 2018) - Prasad, Kameshwar; Siemieniuk, Reed; Hao, Qiukui; Guyatt, Gordon; O'Donnell, Martin; Lytvyn, Lyubov; Heen, Anja Fog; Agoritsas, Thomas; Vandvik, Per Olav; Gorthi, Sankar Prasad; Fisch, Loraine; Jusufovic, Mirza; et al.
Abstract : What is the role of dual antiplatelet therapy after high risk transient ischaemic attack or minor stroke? Specifically, does dual antiplatelet therapy with a combination of aspirin and clopidogrel lead to a greater reduction in recurrent stroke and death over the use of aspirin alone when given in the first 24 hours after a high risk transient ischaemic attack or minor ischaemic stroke? An expert panel produced a strong recommendation for initiating dual antiplatelet therapy within 24 hours of the onset of symptoms, and for continuing it for 10-21 days. Current practice is typically to use a single drug: